Metacarpal Position and Lunate Facet Screw Fixation in Dorsal Wrist-Spanning Bridge Plates for Intra-Articular Distal Radial Fracture: A Biomechanical Analysis. (4th March 2020) - Guerrero, Evan M.; Lauder, Alexander; Federer, Andrew E.; Glisson, Richard; Richard, Marc J.; Ruch, David S.
Abstract : Background: A dorsal wrist-spanning plate (DWSP) can be affixed to the second or third metacarpal, depending on the morphology of the distal radial fracture (DRF) and on surgeon preference, but comparative biomechanical analyses between these methods are limited. This biomechanical study compared fixation to the second metacarpal versus the third metacarpal as measured by lunate facet fragment displacement in a cadaveric model of an axially loaded intra-articular DRF. The construct rigidity with the addition of an intrafragmentary lunate facet locking screw was also evaluated. Methods: A sample size of 14 cadaveric matched pairs was calculated to achieve 81.7% power. The 28 limbs were randomized to DWSP fixation to the second metacarpal (Group 1) or third metacarpal (Group 2); each wrist underwent an osteotomy simulating an unstable intra-articular DRF. Limbs were tested at axial loads of 50, 100, 150, 200, 250, and 300 N. Lunate facet displacement from the metaphyseal fragment at each load was measured with use of differential variable reluctance transducers. After initial testing, a locking screw was placed through the plate into the lunate facet fragment in the third metacarpal group (Group 3). Displacement measurements were repeated for all loads. Paired 2-tailed t tests with Bonferroni correction (significance, p < 0.008) were performed to assess differences in fragment stability between groups. Results: The average fracture displacement at 300 N was 0.8 mm in Group 1, 0.4 mm in Group 2, and 0.2 mm in Group 3. Plating to the third metacarpal more effectively resisted displacement compared with the second metacarpal at all axial loads (p < 0.008). The addition of a lunate facet screw further stiffened the construct at loads of ≥200 N (p < 0.008). Conclusions: Plate fixation to the third metacarpal with an intrafragmentary screw was the most biomechanically favorable construct, although other factors may favor an alternative distal fixation site. Mean displacement of the lunate facet fragment at 300 N was <1 mm in all groups. Clinical Relevance: The present study demonstrated that a DWSP affixed to the third metacarpal with an intrafragmentary screw provides the most effective stabilization of the lunate facet fragment in intra-articular DRFs. This study validates the use of intrafragmentary screws to increase stability in DWSP fixation.